STUDI KASUS TENTANG PESERTA DIDIK YANG BERPERILAKU AGRESIF DI KELAS X SMAK ABDI WACANA - Betalia Betalia; Yuline Yuline; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractA common problem in this study is how to help students who behave aggressively in the Abdi Wacana Kristen  School in Pontianak. The general objective of this research is to describe the relief effort that will be given to students who behave aggressively at Abdi Wacana Kristen High School in Pontianak. The theoretical benefits of research are expected to be beneficial for the development of the science of counseling guidance and can enrich the concepts of guidance, especially the study of counseling guidance regarding children who behave aggressively and have problems in school. This research method is descriptive in the form of case study research. The case subjects in this study were two people. Data collection techniques in this study were observation, interviews, documentaries and home visits. The data collection tools of this study were observation guidelines, interview guides, and reports on the results of home visits. The conclusion of this research is that the two individuals who behave aggressively both verbally and non-verbally are caused by several different backgrounds and factors that affect both internally and externally. Case subjects 1 The dominant causative factors are (a) Internal factors: anger; (b) external factors: a) Over-indulging, b) Generation gap and c) Struggling. While the factors causing the dominant case II subjects are (a) Internal factors: Mind and Emotion; (b) external factors: lack of active social relations. The alternative assistance provided is case I subjects using the RET counseling model and case II subjects using the Behavioral counseling model approach. The results obtained after being given assistance are that the subjects of cases I and II have undergone a change that is already showing positive behavior. Suggestions for case I subjects and case II subjects to continue to run alternatives that have been given in earnest so that the changes that occur can make both feel better than before.  Keywords : Aggressive, Case Studies, Learners